Bearing and energy storage integrated cement-based structure battery and preparation method thereof
By using controlled phase separation technology and water glass adhesive in cement-based structure batteries, a high-pass conduction electrolyte interface is formed, which solves the problem of insufficient performance of traditional cement-based structure batteries and realizes high-performance cement-based structure batteries.
Patent Information
- Application Number
- CN202411571751.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-06
AI Technical Summary
Traditional cement-based structure batteries have problems with low ionic conductivity, high resistance and lack of electrodes suitable for cement environments, which leads to limitations in their applications in buildings, making it difficult to achieve high mechanical load-bearing strength, high capacity, stable power holding and excellent cycling performance.
Controlled phase separation technology is used to form a polymer-strong alkali network as the electrolyte, and water glass is used as the adhesive for the positive and negative electrodes. Through the good interface between the polymer-cement slurry electrolyte and the positive and negative electrodes, a high-pass conduction ion channel is formed, improving the overall performance of the battery.
It realizes the high mechanical load-bearing strength, high capacity, stable power holding and excellent cycle performance of cement-based structure batteries, and is suitable for storing and releasing renewable energy as building materials.
Smart Images

Figure BDA0005120632880000141 
Figure HDA0005120632890000011 
Figure HDA0005120632890000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of cement-based batteries for construction, and in particular relates to a cement-based structural battery integrating load bearing and energy storage and a preparation method thereof. Background Art
[0002] In order to cope with the depletion and pollution of traditional energy, the application scale of new energy such as solar energy and wind energy has increased dramatically. However, the intermittent and volatile nature of new energy has led to a mismatch between energy supply and demand. In the application process of new energy, energy storage materials and equipment are needed to store the electricity generated by new energy. Future advanced building materials should have multifunctional intelligent characteristics, such as collecting and storing renewable energy such as solar energy and wind energy. Using structures and buildings as energy and storage devices has great innovative significance. Due to the large volume of buildings, even if the energy storage density per unit volume of the new generation of building materials is not high, its energy storage potential is considerable. However, due to the low ion conductivity, high resistance, and lack of electrodes adapted to the cement environment of traditional cement, the current development direction of cement-based structural energy storage materials tends to be cement-based supercapacitors. The low energy density and poor power retention of capacitors severely limit the application of cement-based structured energy storage materials in buildings. It is still very difficult to achieve cement-based structural batteries with high mechanical bearing strength, high capacity, stable power retention, and excellent cycle.
[0003] Therefore, cement-based structural batteries need to be developed. Summary of the invention
[0004] In view of the current lack of cement-based structural battery technology, the purpose of the present invention is to provide a cement-based structural battery with integrated load-bearing and energy storage and a preparation method thereof. The cement-based structural battery of the present invention has high mechanical load-bearing strength, high capacity, stable power retention and excellent cycle.
[0005] The technical solution of the present invention is as follows:
[0006] A method for preparing a cement-based structural battery with integrated load-bearing and energy storage, comprising the steps of:
[0007] 1) mixing a polymer solution, cement and fine sand to obtain a polymer-cement slurry electrolyte;
[0008] The polymer solution is obtained by dissolving a polymer and a strong base in water, or by dissolving a polymer, a strong base and a sulfide in water, or by dissolving a polymer, a strong base, an inorganic sulfide and a chemical cross-linking agent in water;
[0009] The polymer is one or more of PVA or PAA; the strong base is one or more of KOH and NaOH; the sulfide is one or more of Na2S or K2S; the chemical crosslinking agent is one or more of TEAC (tetraethylammonium chloride) and PEGDGE (polyethylene glycol diglycidyl ether);
[0010] 2) Preparation of positive electrode sheet;
[0011] 3) Preparation of negative electrode sheet;
[0012] 4) placing the polymer-cement slurry electrolyte on the surface of the positive electrode sheet and the surface of the negative electrode sheet respectively, then stacking the positive electrode sheet and the negative electrode sheet in sequence, placing them in a mold for curing, and standing to obtain a cement-based structural battery with integrated load-bearing and energy storage.
[0013] The amount of each substance in the polymer solution in step 1) is calculated by weight:
[0014] Polymer 8-10 parts
[0015] 30-40 parts of strong alkali
[0016] 190-210 parts of water;
[0017] When inorganic sulfide is contained, the amount of sulfide is 0.5-1 part;
[0018] When a chemical crosslinking agent is contained, the amount of the chemical crosslinking agent is 0.1-0.5 parts.
[0019] The mixing in step 1) specifically involves mixing a solution of a polymer and a strong base, cement and fine sand at 90-95° C., then cooling to 2-5° C., slowly adding cold water during the cooling process to obtain a cement slurry containing a liquid-solid mixed phase.
[0020] When the polymer solution contains inorganic sulfide, the inorganic sulfide is added together with the cold water; when the polymer solution contains a chemical cross-linking agent, the chemical cross-linking agent is added together with the cold water.
[0021] The cement slurry containing a liquid-solid mixed phase is prepared under stirring conditions at a stirring speed of 135-165 r / min.
[0022] The mixing time at 90-95°C is 1 min-2 min; the cooling to 2-5°C means cooling to 2-5°C within 5-10 min; after adding cold water and cooling to 2-5°C, stirring and mixing, the stirring and mixing time is 15-20 min.
[0023] The mixing of the solution prepared by polymer and strong alkali, cement and fine sand at 90-95°C refers to stirring the polymer, strong alkali and water at 85-95°C at a rotation speed of 240-260r / min for 1.5-2h to prepare a solution; dry mixing cement and fine sand at 90-95°C at a rotation speed of 60-70r / min for 5-10min to obtain a cement-fine sand mixture; and mixing the above solution and cement-fine sand mixture at 90-95°C.
[0024] The solution prepared by the polymer and the strong base refers to stirring the polymer and a part of water at 85-95°C at a speed of 240-260r / min for 40-50min to obtain an aqueous solution of the polymer; the strong base is dissolved in another part of water to obtain a strong base solution; and the strong base solution and the aqueous solution of the polymer are mixed for 50-70min under the condition of constant temperature and speed to obtain the desired solution.
[0025] The mass ratio of the cold water to the polymer is (60-80):(8-10).
[0026] The amounts of polymer, cement and fine sand in the polymer solution in step 1) are calculated by weight: polymer: 8-10 parts; cement: 490-510 parts; fine sand: 140-160 parts.
[0027] The molecular weight of the polymer PVA is 1000-10000, and the molecular weight of PAA is 10000-500000.
[0028] The positive electrode sheet in step 2) is prepared by the following method:
[0029] S1: Evenly mix the positive electrode material, conductive agent, adhesive and solvent to obtain positive electrode active material slurry; S2: Apply the positive electrode active material slurry to the surface of the conductive substrate, form a film, and dry it to obtain a positive electrode sheet.
[0030] The positive electrode material is one or more of nickel hydroxide, transition metal (eg, cobalt), transition metal oxide (cobalt oxide), and transition metal hydroxide.
[0031] The conductive agent is one or more of graphite and carbon nanotubes.
[0032] The adhesive is potassium water glass or sodium water glass, and the modulus of the water glass is 2.0-3.3.
[0033] The solvent is water.
[0034] The mass ratio of the positive electrode material, the conductive agent and the binder is (8-9.5): (0.5-1): (3-6).
[0035] The mass ratio of the positive electrode material to the solvent is (8-9.5): (0.4-0.8). The coating amount of the positive electrode active material slurry is 0.3-0.4 g / cm 2 The positive electrode active material slurry is coated on both surfaces of the conductive substrate.
[0036] The conductive agent is divided into two parts, one part is mixed with the positive electrode material, and the other part is mixed with the binder and the solvent.
[0037] The conductive substrate is a metal sheet such as foamed nickel, copper foil, aluminum foil, etc.
[0038] The negative electrode sheet in step 3) is prepared by the following method: uniformly mixing the negative electrode active material, the conductive agent and the binder to obtain the negative electrode active material slurry; coating the negative electrode active material slurry on the surface of the conductive substrate, forming a film, and drying to obtain the negative electrode sheet.
[0039] The negative electrode active material is one or more of iron, iron oxide, ferroferric oxide, carbonyl iron, ferrous sulfide, bismuth sulfide, zinc, zinc oxide, zinc-containing alloy, and iron-containing alloy;
[0040] The conductive agent is one or more of carbon nanotubes and graphite.
[0041] The binder is one or more of potassium water glass and sodium water glass.
[0042] The coating amount of the negative electrode active material slurry is 0.35-0.45 g / cm 2 .
[0043] The mass ratio of the negative electrode active material, the conductive agent and the binder is (7.5-10): (0-0.5): (3-5.5).
[0044] The conductive substrate is a metal sheet such as foamed nickel, copper foil, aluminum foil, etc.
[0045] The curing in step 4) refers to closed curing at 0°C-3°C for 6-24 hours. The standing refers to room temperature for 12-24 hours.
[0046] A load-bearing and energy-storage integrated cement-based structural battery is prepared by the above preparation method.
[0047] Application of the battery of the present invention in construction.
[0048] Beneficial effects:
[0049] 1) The present invention adopts controlled phase separation technology to make the elastic phase separation of the polymer-strong base network (such as PVA-KOH) network proceed earlier than cement hydration. The cement adaptively becomes the skeleton of the polymer-strong base network during the hydration process. The two have a good interface and can form a continuous high-throughput ion channel.
[0050] 2) The positive and negative electrodes of the present invention use water glass as a binder. Due to its good compatibility, it can form a strong electrolyte-electrode interface, greatly improving the conductivity of ions on the interface.
[0051] 3) The preparation process of the present invention is simple to operate, highly repeatable, and the raw materials used are environmentally friendly and inexpensive.
[0052] In summary, the cement-based structural battery of the present invention has high mechanical bearing strength, high capacity, stable power retention and excellent cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 The structural schematic diagram of the cement-based structural battery of the present invention; 1-positive electrode sheet, 2-negative electrode sheet, 3-electrolyte, 4-leading portion of the matrix (current collector); the two upper figures are schematic cross-sectional views, and the lower figure is a top view;
[0054] Figure 2 Schematic diagram of the present invention using a circular component mold to prepare a cement-based structural battery; 5- circular component No. 1 of the mold, 6- semicircular component No. 2 of the mold, 7- positive electrode sheet, 8- negative electrode sheet;
[0055] Figure 3 Schematic diagram of the present invention using a square component mold to prepare a cement-based structural battery; 9-square component No. 1 of the mold, 10-right-angled triangle component No. 2 of the mold, 11-positive electrode sheet, 12-negative electrode sheet;
[0056] Figure 4 EIS (Nyquist plot) of the battery prepared in Example 1;
[0057] Figure 5 EIS of the battery prepared in Example 2;
[0058] Figure 6 EIS of the battery prepared in Example 3;
[0059] Figure 7 EIS of the battery prepared in Comparative Example 1;
[0060] Figure 8 EIS of the battery prepared in Comparative Example 2;
[0061] Fig. 9 EIS of the battery prepared in Comparative Example 3;
[0062] Fig.10 LSV curves of the batteries prepared in Example 1, Comparative Example 1 and Comparative Example 3;
[0063] Fig.11CV curves of the batteries prepared in Example 1, Comparative Example 1 and Comparative Example 3;
[0064] Fig.12 XRD pattern of the positive electrode sheet prepared in Example 1;
[0065] Fig.13 XRD pattern of the negative electrode sheet prepared in Example 1;
[0066] Fig.14 The voltage-discharge capacity curves of the batteries prepared in Examples 1 to 3;
[0067] Fig.15 The voltage-discharge capacity curve of the battery prepared in Example 4;
[0068] Fig.16 The voltage-discharge capacity curves of the batteries prepared in Comparative Examples 1 to 3;
[0069] Fig.17 This is a test diagram of the charge and discharge cycle performance of the battery prepared in Example 1;
[0070] Fig.18 The power retention performance test curves of Examples 1 and 2 and commercial nickel-iron batteries;
[0071] Fig.19 This is a picture of a light-emitting LED after the batteries prepared in Examples 5 and 6 are connected in series. DETAILED DESCRIPTION
[0072] The present invention is further described in detail below in conjunction with specific examples, but the embodiments of the present invention are not limited thereto.
[0073] Figure 1 The cement-based structural battery of the present invention is a schematic diagram; the two figures above are schematic cross-sectional views, and the figure below is a top view. The cement-based structural battery of the present invention includes a positive electrode sheet and a negative electrode sheet and an electrolyte covering the positive electrode sheet and the negative electrode sheet. The positive electrode sheet and the negative electrode sheet are stacked in sequence, and an electrolyte is provided between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet and the negative electrode sheet are respectively provided with a lead-out portion of the matrix, i.e., a current collector.
[0074] Figure 2 The schematic diagram of the present invention using a circular component mold to prepare a cement-based structural battery; the mold of the present invention includes two components No. 1 and four semicircular components No. 2; the two semicircular components No. 2 can be assembled into a circular component No. 3, the circular component No. 3 is hollow, and the component No. 1 is a circular solid; the two circular components No. 3 are stacked in sequence, forming a hollow in the middle, and the component No. 1 is located at both ends of the stacked circular components No. 3 to seal the port. The positive electrode sheet is located in one circular component No. 3, and the negative electrode sheet is located in another circular component No. 3, and the cavity of the circular component No. 3 between the negative electrode sheet and the positive electrode sheet is provided with electrolyte.
[0075] Figure 3 The schematic diagram of the present invention using a square component mold to prepare a cement-based structural battery. The mold of the present invention includes two square components No. 1 and four right-angled triangle components No. 2; two right-angled triangle components No. 2 can be assembled into a square component No. 3, the square component No. 3 is hollow, and component No. 1 is a square solid; two square components No. 3 are stacked in sequence, forming a hollow in the middle, and component No. 1 is located at both ends of the two square components No. 3 after stacking, sealing the port. The positive electrode sheet is located in the square component No. 3, and the negative electrode sheet is located in another square component No. 3. Electrolytes are provided between the negative electrode sheet and the positive electrode sheet and in the cavity of the square component No. 3.
[0076] Example 1: (Polymer solution is PVA-KOH)
[0077] Dissolve 10g PVA1799 in 90g deionized water, heat in a water bath at 95℃ and stir at 250r / min for 50min to obtain PVA solution; dissolve 30g KOH solid in 110g water to obtain KOH solution; when the PVA solution is light milky white, slowly drip the KOH solution into the PVA solution and keep heating and stirring for 50min until the mixed solution is transparent and light yellow to obtain PK solution. Premix 490g cement (PO42.5R) and 140g fine sand at 70r / min for 10min at 90℃ to obtain a cement-fine sand mixture; add the cement-fine sand mixture to the PK solution at 90℃ and stir at 145r / min for 2min. After this process, turn on the cooler and slowly add 60g deionized water at 2℃ to reduce the slurry temperature to 2℃, keep stirring at 145r / min for 16min to obtain a polymer-cement slurry.
[0078] The positive electrode sheet was prepared as follows: 0.36 g Co, 8.7 g Ni(OH )2 Grind for 15 minutes until the powder is dark green, add 0.43g 100 mesh graphite and continue grinding for 13 minutes until the powder is gray-green to obtain a mixed powder. Weigh 4.3g of low-temperature potassium water glass with a modulus of 3.3, add 0.7g deionized water and 0.28g 100 mesh graphite, stir evenly, and obtain a water glass dispersion. Add the mixed powder to the potassium water glass dispersion twice, stir until it is a uniform slurry, and evenly scrape it on a 2mm*2mm square clean foam nickel substrate (0.35g / cm 2 After the electrode is formed into a film, place it under a 320W drying light source for 30 minutes until the electrode surface turns dark green and the center of the area hardens, and then seal it in a bag.
[0079] The preparation method of the negative electrode sheet is as follows: 0.6g FeS and 6.8g iron powder are ground for 10 minutes until the powder is uniform, and 2.1g Fe3O4 is added and ground for 20 minutes until the powder is dark orange to obtain a mixed powder. The mixed powder is added twice to 4.55g low-temperature potassium water glass with a modulus of 3.3, stirred to a uniform slurry, and evenly coated on a 2mm*2mm square clean nickel foam substrate (0.4g / cm 2 ). After the electrode is coated, let it stand for 13 minutes. After the electrode surface forms a film, place it under a 320W drying light source for 27 minutes until the center of the electrode area hardens and seal it in a bag.
[0080] The positive and negative electrodes are assembled using polymer-cement slurry (i.e., the polymer-cement slurry is coated on the surface of the positive electrode and the negative electrode, respectively), placed in a mold, sealed and cured at 2°C for 24 hours, and left to stand at room temperature for 24 hours to obtain a cement-based structural battery.
[0081] Example 2: (Polymer solution is PVA-PAA-KOH)
[0082] 7.8g PVA1799 and 0.2g PAA (polyacrylic acid, molecular weight 450000) were dissolved in 90g deionized water, heated in a water bath at 85℃ and stirred at 260r / min for 50min to obtain a polymer solution; 40g KOH solid was dissolved in 115g water to obtain a KOH solution; when the polymer solution was light milky white, the KOH solution was slowly dripped into the polymer solution and kept heated and stirred for 70min to obtain a PKA solution. 510g cement (PO42.5R) and 160g fine sand were premixed at 65r / min for 8min at 95℃ to obtain a cement-fine sand mixture; the cement-fine sand mixture was added to the PKA solution at 95℃ and stirred at 140r / min for 1min30s. After this process, the cooler was turned on and 80g deionized water at 5℃ was slowly added to reduce the slurry temperature to 5℃, and stirred at 140r / min for 20min to obtain a polymer-cement slurry.
[0083] The preparation method of the positive electrode sheet is as follows: grind 0.40g Co and 8.0g Ni(OH)2 for 15min until the powder is dark green, add 0.43g 100-mesh graphite and continue grinding for 13min until the powder is gray-green to obtain a mixed powder. Weigh 4.3g of low-temperature potassium water glass with a modulus of 3.3, add 0.7g deionized water and 0.25g 100-mesh graphite, stir evenly, and obtain a potassium water glass mixed solution. Add the mixed powder to the potassium water glass mixed solution twice, stir until it is a uniform slurry, and evenly scrape it on a 2mm*2mm square clean foam nickel substrate (0.35g / cm 2After the electrode is formed into a film, place it under a 320W drying light source for 28 minutes until the electrode surface turns dark green and the center of the area hardens, and then seal it in a bag.
[0084] The preparation method of the negative electrode sheet is as follows: 0.6g FeS and 6.8g iron powder are ground for 10 minutes until the powder is uniform, and 2.1g Fe3O4 is added and ground for 20 minutes to obtain a mixed powder. The mixed powder is added twice to 4.55g low-temperature potassium water glass with a modulus of 3.3, stirred to a uniform slurry, and evenly coated on a 2mm*2mm square clean foam nickel substrate (0.4g / cm 2 ). After the electrode is coated, let it stand for 15 minutes. After the electrode surface forms a film, place it under a 320W drying light source for 27 minutes until the center of the electrode area hardens, and then seal it in a bag.
[0085] The positive and negative electrodes were assembled using polymer-cement slurry, placed in a special mold, sealed and cured at 0°C for 6 hours, and left to stand at room temperature for 12 hours to obtain a cement-based structural battery.
[0086] Example 3: (Polymer solution is PVA-KOH-K2S)
[0087] Dissolve 9.8g PVA1799 in 90g deionized water, heat in a water bath at 92℃ and stir at 255r / min for 4min to obtain a polymer solution; dissolve 33.6g KOH solid in 110g water to obtain a KOH solution. When the PVA solution is light milky white, slowly drip the KOH solution into the PVA solution and keep heating and stirring for 50min to obtain a PK solution. Premix 500g cement (PO42.5R) and 150g fine sand at 60r / min for 5min at 92℃ to obtain a cement-fine sand mixture. Keep 92℃ and add the cement-fine sand mixture to the PK solution, stir at 135r / min for 1min45s. After this process, turn on the cooler and slowly add 3℃65g deionized water and 0.8g K2S to reduce the slurry temperature to 3℃, keep stirring at 135r / min for 18min to obtain a polymer-cement slurry.
[0088] The preparation method of the positive electrode sheet is as follows: grind 0.36g Co and 8.7g Ni(OH)2 for 15min until the powder is dark green, add 0.43g 100-mesh graphite and continue grinding for 13min until the powder is gray-green to obtain a mixed powder. Weigh 4.3g of low-temperature potassium water glass with a modulus of 3.3, add 0.7g deionized water and 0.28g 100-mesh graphite, stir evenly, and obtain a potassium water glass mixed solution. Add the mixed powder to the potassium water glass mixed solution twice, stir until it is a uniform slurry, and evenly scrape it on a 2mm*2mm square clean foam nickel substrate (0.35g / cm 2After the electrode is formed into a film, place it under a 320W drying light source for 30 minutes until the electrode surface turns dark green and the center of the area hardens, and then seal it in a bag.
[0089] The preparation method of the negative electrode sheet is as follows: 0.6g FeS and 6.8g iron powder are ground for 10 minutes until the powder is uniform, and 2.1g Fe3O4 is added and ground for 20 minutes to obtain a mixed powder. The mixed powder is added twice to 4.55g low-temperature potassium water glass with a modulus of 3.3, stirred to a uniform slurry, and evenly coated on a 2mm*2mm square clean foam nickel substrate (0.4g / cm 2 After the electrode is coated, let it stand for 15 minutes. After the electrode surface forms a film, place it under a 320W drying light source for 29 minutes until the center of the electrode area hardens and seal it in a bag.
[0090] The positive and negative electrodes were assembled using polymer-cement slurry, placed in a special mold, sealed and cured at 1°C for 21 hours, and left to stand at room temperature for 18 hours to obtain a cement-based structural battery.
[0091] Example 4: (Polymer solution is PVA-KOH)
[0092] Dissolve 10g PVA1799 in 90g deionized water, heat in a water bath at 95℃ and stir at 250r / min for 50min to obtain a polymer solution; dissolve 33.6g KOH solid in 110g water to obtain a KOH solution. When the PVA solution is light milky white, slowly drip the KOH solution into the PVA solution and keep heating and stirring for 50min to obtain a PK solution. Premix 500g cement (PO42.5R) and 150g fine sand (0.25-0.35mm) at 70r / min for 10min at 90℃ to obtain a cement-fine sand mixture. Keep 95℃ and add the cement-fine sand mixture to the PK solution, stir at 145r / min for 2min, turn on the cooler after this process and slowly add 2℃65g deionized water to reduce the slurry temperature to 2℃, keep stirring at 145r / min for 16min to obtain a polymer-cement slurry.
[0093] The preparation method of the positive electrode sheet is as follows: grind 1.44g Co and 34.8g Ni(OH)2 for 15min until the powder is dark green, add 1.72g 100-mesh graphite (acting as an electron path to reduce the particle interface resistance) and continue grinding for 13min until the powder is gray-green to obtain a mixed powder. Weigh 17.2g of low-temperature potassium water glass with a modulus of 3.3, add 2.8g deionized water and 1.12g 100-mesh graphite, stir evenly, and obtain a potassium water glass mixed solution. Add the mixed powder to the potassium water glass mixed solution twice, stir until it is a uniform slurry, and evenly scrape it on a 80mm*80mm square clean foam nickel substrate (0.32g / cm2 After the electrode is film-formed, it is placed under a 320W drying light source for 33 minutes until the electrode surface is dark green and the center of the area is hardened, and then sealed and bagged. The present invention pre-disperses a portion of graphite in the adhesive to reduce the film-forming effect of the adhesive and reduce the resistance of the adhesive.
[0094] The preparation method of the negative electrode sheet is as follows: 2.4g FeS and 27.2g iron powder are added to a mortar in sequence, and ground for 12 minutes until the powder is uniform. 8.4g Fe3O4 is added and ground for 20 minutes until the powder is dark orange to obtain a mixed powder. The mixed powder is added twice to 18.2g low-temperature potassium water glass with a modulus of 3.3, stirred to a uniform slurry, and evenly coated on a 80mm*80mm square clean nickel foam substrate (0.36g / cm 2 ), note that the coating method is scraping. After coating, the electrode is left to stand for 13 minutes, and after the electrode surface is filmed, it is placed under a 320W drying light source for 27 minutes until the center of the electrode area hardens, and then sealed and bagged.
[0095] The positive and negative electrodes are assembled using polymer-cement slurry, placed in a special mold, sealed and cured at 2°C for 24 hours, and left to stand at room temperature for 24 hours to obtain a cement-based structural battery.
[0096] Example 5: (Polymer solution is PVA-KOH)
[0097] 9.5g PVA1799 was dissolved in 90g deionized water, heated in a water bath at 95℃ and stirred at 250r / min for 50min to obtain PVA solution; 30g KOH solid was dissolved in 110g water to obtain KOH solution; when the PVA solution was light milky white, the KOH solution was slowly dripped into the PVA solution and kept heated and stirred for 50min until the mixed solution was transparent and light yellow to obtain PK solution. 490g cement (PO42.5R) and 140g fine sand were premixed at 70r / min for 10min at 90℃ to obtain a cement-fine sand mixture; the cement-fine sand mixture was added to the PK solution at 90℃ and stirred at 145r / min for 2min. After this process, the cooler was turned on and 60g deionized water at 2℃ was slowly added to reduce the slurry temperature to 2℃, and stirred at 145r / min for 16min to obtain a polymer-cement slurry.
[0098] The positive electrode sheet was prepared as follows: 0.36 g Co, 8.7 g Ni(OH )2Grind for 15 minutes until the powder is dark green, add 0.43g 100 mesh graphite and continue grinding for 13 minutes until the powder is gray-green to obtain a mixed powder. Weigh 4.3g of low-temperature potassium water glass with a modulus of 3.3, add 0.7g deionized water and 0.28g 100 mesh graphite, stir evenly, and obtain a water glass dispersion. Add the mixed powder to the potassium water glass dispersion twice, stir until it is a uniform slurry, and evenly scrape it on a 2mm*2mm square clean foam nickel substrate (0.35g / cm 2 After the electrode is formed into a film, place it under a 320W drying light source for 30 minutes until the electrode surface turns dark green and the center of the area hardens, and then seal it in a bag.
[0099] The preparation method of the negative electrode sheet is as follows: 0.6g FeS and 6.8g iron powder are ground for 10 minutes until the powder is uniform, and 2.1g Fe3O4 is added and ground for 20 minutes until the powder is dark orange to obtain a mixed powder. The mixed powder is added twice to 4.55g low-temperature potassium water glass with a modulus of 3.3, stirred to a uniform slurry, and evenly coated on a 2mm*2mm square clean nickel foam substrate (0.4g / cm 2 ). After the electrode is coated, let it stand for 13 minutes. After the electrode surface forms a film, place it under a 320W drying light source for 27 minutes until the center of the electrode area hardens and seal it in a bag.
[0100] The positive and negative electrodes are assembled using polymer-cement slurry (i.e., the polymer-cement slurry is coated on the surface of the positive electrode and the negative electrode, respectively), placed in a mold, sealed and cured at 2°C for 24 hours, and left to stand at room temperature for 24 hours to obtain a cement-based structural battery.
[0101] Example 6: (Polymer solution is PVA-KOH)
[0102] 9.7g PVA1799 was dissolved in 90g deionized water, heated in a water bath at 95℃ and stirred at 250r / min for 50min to obtain PVA solution; 30g KOH solid was dissolved in 110g water to obtain KOH solution; when the PVA solution was light milky white, the KOH solution was slowly dripped into the PVA solution and kept heated and stirred for 50min until the mixed solution was transparent and light yellow to obtain PK solution. 490g cement (PO42.5R) and 140g fine sand were premixed at 70r / min for 10min at 90℃ to obtain a cement-fine sand mixture; the cement-fine sand mixture was added to the PK solution at 90℃ and stirred at 145r / min for 2min. After this process, the cooler was turned on and 60g deionized water at 2℃ was slowly added to reduce the slurry temperature to 2℃, and stirred at 145r / min for 16min to obtain a polymer-cement slurry.
[0103] The positive electrode sheet was prepared as follows: 0.36 g Co, 8.7 g Ni(OH )2 Grind for 15 minutes until the powder is dark green, add 0.43g 100 mesh graphite and continue grinding for 13 minutes until the powder is gray-green to obtain a mixed powder. Weigh 4.3g of low-temperature potassium water glass with a modulus of 3.3, add 0.7g deionized water and 0.28g 100 mesh graphite, stir evenly, and obtain a water glass dispersion. Add the mixed powder to the potassium water glass dispersion twice, stir until it is a uniform slurry, and evenly scrape it on a 2mm*2mm square clean foam nickel substrate (0.35g / cm 2 ). After the electrode is formed into a film, place it under a 320W drying light source for 30 minutes until the electrode surface turns dark green and the center of the area hardens, and then seal it in a bag.
[0104] The preparation method of the negative electrode sheet is as follows: 0.6g FeS and 6.8g iron powder are ground for 10 minutes until the powder is uniform, and 2.1g Fe3O4 is added and ground for 20 minutes until the powder is dark orange to obtain a mixed powder. The mixed powder is added twice to 4.55g low-temperature potassium water glass with a modulus of 3.3, stirred to a uniform slurry, and evenly coated on a 2mm*2mm square clean nickel foam substrate (0.4g / cm 2 ). After the electrode is coated, let it stand for 13 minutes. After the electrode surface forms a film, place it under a 320W drying light source for 27 minutes until the center of the electrode area hardens and seal it in a bag.
[0105] The positive and negative electrodes are assembled using polymer-cement slurry (i.e., the polymer-cement slurry is coated on the surface of the positive electrode and the negative electrode, respectively), placed in a mold, sealed and cured at 2°C for 24 hours, and left to stand at room temperature for 24 hours to obtain a cement-based structural battery.
[0106] Comparative Example 1: (The polymer solution is PVA-KOH, there is no cooling process, it is directly mixed and stirred, and then placed in a 2°C environment for curing)
[0107] Dissolve 10g PVA1799 in 90g deionized water, heat in a water bath at 95℃ and stir at 250r / min for 50min to obtain a polymer solution; dissolve 33.6g KOH solid in 110g water to obtain a KOH solution. When the PVA solution is light milky white, slowly drip the KOH solution into the PVA solution and keep heating and stirring for 50min to obtain a PK solution. Premix 500g cement (PO42.5R) and 150g fine sand at 70r / min for 10min at 90℃ to obtain a cement-fine sand mixture. Add the cement-fine sand mixture and 65g normal temperature deionized water to the PK solution at room temperature, stir at 145r / min for 18min to obtain a polymer-cement slurry.
[0108] The preparation method of the positive electrode is as follows: grind 0.36g Co and 8.7g Ni(OH)2 for 15min until the powder is dark green, add 0.43g 100-mesh graphite and continue grinding for 13min until the powder is gray-green to obtain a mixed powder. Weigh 4.3g of low-temperature potassium water glass with a modulus of 3.3, add 0.7g deionized water and 0.28g 100-mesh graphite, stir evenly, and obtain a potassium water glass mixed solution. Add the mixed powder to the potassium water glass mixed solution twice, stir until it becomes a uniform slurry, and evenly scrape it on a 2mm*2mm square clean foam nickel substrate. After the electrode is formed into a film, place it under a 320W drying light source for 30min until the electrode surface is dark green and the center of the area is hardened, and seal it in a bag.
[0109] The preparation method of the negative electrode sheet is as follows: grind 0.6g FeS and 6.8g iron powder for 10 minutes until the powder is uniform, add 2.1g Fe3O4 and continue grinding for 20 minutes to obtain a mixed powder. Add the mixed powder twice to 4.55g low-temperature potassium water glass with a modulus of 3.3, stir until it becomes a uniform slurry, and evenly apply it on a 2mm*2mm square clean foam nickel substrate. After the electrode is applied, let it stand for 13 minutes. After the electrode surface forms a film, place it under a 320W drying light source for 27 minutes until the center of the electrode area hardens, and seal it in a bag.
[0110] The positive and negative electrodes were assembled using polymer-cement slurry, placed in a mold, sealed and cured at 2°C for 24 hours, and left to stand at room temperature for 24 hours to obtain a cement-based structural battery.
[0111] Comparative Example 2: (The polymer solution is PVA-KOH, there is a cooling process, and curing at room temperature)
[0112] Dissolve 10g PVA1799 in 90g deionized water, heat in a water bath at 95℃ and stir at 250r / min for 50min to obtain a polymer solution; dissolve 33.6g KOH solid in 110g water to obtain a KOH solution. When the PVA solution is light milky white, slowly drip the KOH solution into the PVA solution and keep heating and stirring for 50min to obtain a PK solution. Premix 500g cement (PO42.5R) and 150g fine sand at 70r / min for 10min at 90℃ to obtain a cement-fine sand mixture. Add the cement-fine sand mixture to the PK solution at 95℃ and stir at 145r / min for 2min. After this process, turn on the cooler and slowly add 65g deionized water at 2℃ to reduce the slurry temperature to 2℃. Keep stirring at 145r / min for 16min to obtain a polymer-cement slurry.
[0113] The preparation method of the positive electrode is as follows: grind 0.36g Co and 8.7g Ni(OH)2 for 15min, add 0.43g 100-mesh graphite and continue grinding for 13min until the powder is gray-green to obtain a mixed powder. Weigh 4.3g of low-temperature potassium water glass with a modulus of 3.3, add 0.7g deionized water and 0.28g 100-mesh graphite, stir evenly, and obtain a potassium water glass mixed solution. Add the mixed powder to the potassium water glass mixed solution twice, stir until it becomes a uniform slurry, and evenly scrape it on a 2mm*2mm square clean foam nickel substrate. After the electrode is formed into a film, place it under a 320W drying light source for 30min until the electrode surface is dark green and the center of the area is hardened, and seal it in a bag.
[0114] The preparation method of the negative electrode sheet is as follows: grind 0.6g FeS and 6.8g iron powder for 10 minutes, add 2.1g Fe3O4 and continue grinding for 20 minutes to obtain a mixed powder. Add the mixed powder twice to 4.55g low-temperature potassium water glass with a modulus of 3.3, stir until it becomes a uniform slurry, and evenly apply it on a 2mm*2mm square clean foam nickel substrate. After the electrode is applied, let it stand for 13 minutes. After the electrode surface forms a film, place it under a 320W drying light source for 27 minutes until the center of the electrode area hardens, and seal it in a bag.
[0115] The positive and negative electrodes were assembled using polymer-cement slurry, placed in a mold, and allowed to stand at room temperature for 48 hours to obtain a cement-based structural battery.
[0116] Comparative Example 3: (Polymer solution is PVA-KOH, no cooling process, room temperature curing)
[0117] Dissolve 10g PVA1799 in 90g deionized water, heat in a water bath at 95℃ and stir at 250r / min for 50min to obtain a polymer solution; dissolve 33.6g KOH solid in 110g water to obtain a KOH solution. When the PVA solution is light milky white, slowly drip the KOH solution into the PVA solution and keep heating and stirring for 50min to obtain a PK solution. Premix 500g cement (PO42.5R) and 150g fine sand at 70r / min for 10min at 90℃ to obtain a cement-fine sand mixture. Add the cement-fine sand mixture and 65g deionized water at room temperature to the PK solution, stir at 145r / min for 18min to obtain a polymer-cement slurry.
[0118] The preparation method of the positive electrode is as follows: grind 0.36g Co and 8.7g Ni(OH)2 for 15min, add 0.43g 100-mesh graphite and continue grinding for 13min to obtain a mixed powder. Weigh 4.3g low-temperature potassium water glass with a modulus of 3.3, add 0.7g deionized water and 0.28g 100-mesh graphite, stir evenly, and obtain a potassium water glass mixed solution. Add the mixed powder to the potassium water glass mixed solution twice, stir until it becomes a uniform slurry, and evenly scrape it on a 2mm*2mm square clean foam nickel substrate. After the electrode is formed into a film, place it under a 320W drying light source for 30min until the electrode surface is dark green and the center of the area is hardened, and then seal it in a bag.
[0119] The preparation method of the negative electrode sheet is as follows: 0.6g FeS and 6.8g iron powder are added to the mortar in turn, and ground for 10 minutes. 2.1g Fe3O4 is added and ground for 20 minutes to obtain a mixed powder. The mixed powder is added twice to 4.55g low-temperature potassium water glass with a modulus of 3.3, stirred to a uniform slurry, and evenly coated on a 2mm*2mm square clean foam nickel substrate. After the electrode is coated, let it stand for 13 minutes. After the electrode surface is filmed, it is placed under a 320W drying light source for 27 minutes until the center of the electrode area hardens, and then sealed and bagged.
[0120] The positive and negative electrodes were assembled using polymer-cement slurry, placed in a mold, and allowed to stand at room temperature for 48 hours to obtain a cement-based structural battery.
[0121] Performance Testing:
[0122] Figures 4 to 9 EIS (Nyquist plots) of the batteries prepared in Examples 1 to 3 and Comparative Examples 1 to 3, respectively.
[0123] EIS (Nyquist plot) reflects the ionic conductivity of the electrolyte and the electrolyte-electrode interface resistance. The higher the ionic conductivity and the lower the electrolyte-electrode interface resistance, the better the performance of the electrolyte.
[0124] From the EIS results, it can be seen that the conductivity of Example 1 is 108mS / cm, the conductivity of Example 2 is 303mS / cm, the conductivity of Example 3 is 165.6mS / cm, the conductivity of Comparative Example 1 is 63.3mS / cm, the conductivity of Comparative Example 2 is 1.926mS / cm, and the conductivity of Comparative Example 3 is 0.166mS / cm.
[0125] It can be seen from Examples 1-3 that the ionic conductivity of the cement-based structured electrolyte after cooling and stirring and low temperature curing is 10 2 On the order of mS / cm.
[0126] From the comparison between Example 1 and Comparative Example 1, it can be seen that the ion conductivity decreases by 41.4% due to the lack of cooling and stirring.
[0127] From the comparison between Example 1 and Comparative Example 2, it can be seen that the ion conductivity decreases by 98.2% due to the lack of low-temperature maintenance.
[0128] From the comparison between Example 1 and Comparative Example 3, it can be seen that the ion conductivity is reduced by 99.8% due to the lack of cooling, stirring and low-temperature curing. That is, the product formed by directly mixing the polymer solution and cement does not have the ability to serve as an electrolyte.
[0129] From the analysis of the interface resistance of Examples 1-3 and Comparative Examples 1-3, most of the values are around 1 ohm, which confirms the enhancement effect of water glass at the electrolyte-electrode interface.
[0130] Fig.10 The LSV curves of the batteries prepared in Example 1 and Comparative Examples 1 and 3 are shown. The longer the LSV window, the more stable the electrolyte. The electrolyte with cooling, stirring and low temperature curing (Example 1) is the most stable.
[0131] Fig.11 The CV curves of the batteries prepared in Example 1 and Comparative Examples 1 and 3. The CV test is conducted by applying a linearly varying potential (voltage) and monitoring the corresponding current response. Comparative Example 1 (no cooling and stirring, but 2-5°C curing) and Comparative Example 3 (no cooling and stirring, but no 2-5°C curing) do not have the reaction peaks shown in Example 1. The reaction peaks of 0.74V and 1.00V correspond to the reduction reaction of the iron pole, and 1.65V corresponds to the oxidation reaction of the nickel pole. Only in Example 1 (both cooling and constant speed stirring and 2-5°C curing electrolyte) is there a complete reaction peak, which proves the feasibility of applying this electrolyte to all-solid-state alkaline batteries. This illustrates the superiority of the temperature-controlled, originally phase-separated cement-based structured electrolyte proposed in the present invention in supporting the electrical reaction of all-solid-state batteries.
[0132] Fig.12 XRD pattern of the positive electrode sheet prepared in Example 1; Fig.13 This is the XRD pattern of the negative electrode sheet prepared in Example 1.
[0133] Fig.14 The voltage-discharge capacity curves of the batteries prepared in Examples 1 to 3 are shown. Fig.15 This is a voltage-discharge capacity curve of the battery prepared in Example 4. Fig.16 The voltage-discharge capacity curves of the batteries prepared in Comparative Examples 1 to 3 are shown.
[0134] Discharge capacity: The battery with cooling and stirring + low temperature maintenance (Examples 1-3) has a capacity of 50 mAh and an area energy density of 12.5 mAh / cm2 , 175Wh / m 2 , that is, a 6m*6m cement wall can store 6.3KWh of electricity. Keeping the electrolyte unchanged and increasing the electrode area (Example 4), the capacity can reach 550mAh. Lack of cooling and stirring (temperature-controlled second step) (Comparative Example 1), the capacity is only 24mAh; lack of low-temperature maintenance (temperature-controlled third step) (Comparative Example 2), the capacity is only 10mAh; lack of both (direct mixing of PK and cement, Comparative Example 3) is only 7mAh. It shows that the temperature-controlled phase separation technology in the present invention plays a very important role in the capacity of all-solid-state cement batteries.
[0135] Fig.17 This is a test diagram of the charge and discharge cycle performance of the battery prepared in Example 1.
[0136] For Example 1 alone, 2 mA / cm 2 The charge and discharge cycles, each cycle involving charging for 1320s and discharging for 1200s, obtained the above cycle test results. The all-solid-state cement-based structural battery of the present invention had no obvious attenuation in the first 500 cycles. After 3000 cycles, the polarization voltage was only 0.3V. The cement battery of the present invention has excellent cycle characteristics and is particularly suitable as a structured energy storage device.
[0137] Fig.18 The power retention performance test curves of Examples 1 and 2 and commercial nickel-iron batteries.
[0138] For Example 1-2, the battery was charged for 3 hours at a charging current of 15 mA, then left to stand, and the open circuit voltage of the battery was measured every 1 hour. By comparing it with the public power retention data of commercial alkaline nickel-iron batteries, it can be found that the voltage retention capacity of the cement-based structural battery (unsealed) of the present invention under air conditions is close to that of commercial batteries. The primary requirement of energy storage devices is stable power retention (a significant feature different from capacitors), so the cement-based structural battery of the present invention can be used as an energy storage device.
[0139] Fig.19 The figure shows the LEDs lit up after the batteries prepared in Examples 5 and 6 were connected in series. For Examples 5-6, after charging at 15 mA for 5 minutes, the red LEDs were lit up in series.
[0140] The mechanical strengths of the cement-based batteries of Examples 1 to 3 are shown in Table 1.
[0141] Table 1 Mechanical strength
[0142]
[0143] As can be seen from Table 1, Examples 1-3 have high and stable compressive and flexural strengths and have the ability to act as a structure. Therefore, the cement-based battery of the present invention can actually be used as a cement-based structural battery, directly as a part of a building (walls, columns, panels), which not only participates in the force, but also can be used as an energy storage device to collect clean energy such as solar energy.
[0144] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a cement-based structural battery with integrated load-bearing and energy storage, characterized in that: Includes steps: 1) mixing a polymer solution, cement and fine sand to obtain a polymer-cement slurry electrolyte; The polymer solution is obtained by dissolving a polymer and a strong base in water, or by dissolving a polymer, a strong base and a sulfide in water, or by dissolving a polymer, a strong base, an inorganic sulfide and a chemical cross-linking agent in water; the polymer is one or more of PVA or PAA; 2) Preparation of positive electrode sheet; 3) Preparation of negative electrode sheet; 4) placing a polymer-cement slurry electrolyte on the surface of the positive electrode sheet and the surface of the negative electrode sheet respectively, then stacking the positive electrode sheet and the negative electrode sheet in sequence, placing them in a mold for curing, and standing to obtain a cement-based structural battery with integrated load bearing and energy storage; The mixing in step 1) specifically involves mixing a solution of a polymer and a strong base, cement and fine sand at 90-95° C., then cooling to 2-5° C., and adding cold water to obtain a cement slurry containing a liquid-solid mixed phase.
2. The method for preparing the cement-based structural battery with integrated load-bearing and energy storage according to claim 1, characterized in that: When the polymer solution contains inorganic sulfide, the inorganic sulfide is added together with the cold water; when the polymer solution contains a chemical crosslinking agent, the chemical crosslinking agent is added together with the cold water; The amount of each substance in the polymer solution in step 1) is calculated by weight: Polymer 8-10 parts 30-40 parts of strong alkali 190-210 parts of water; When inorganic sulfide is contained, the amount of sulfide is 0.5-1 part; When a chemical crosslinking agent is contained, the amount of the chemical crosslinking agent is 0.1-0.5 parts; The amounts of polymer, cement and fine sand in the polymer solution in step 1) are calculated by weight: 8-10 parts of polymer; 490-510 parts of cement; 140-160 parts of fine sand; The curing in step 4) refers to closed curing at 0°C to 3°C.
3. The method for preparing the cement-based structural battery with integrated load-bearing and energy storage according to claim 1, characterized in that: The positive electrode sheet in step 2) is prepared by the following method: S1: uniformly mix the positive electrode material, conductive agent, adhesive and solvent to obtain positive electrode active material slurry; S2: apply the positive electrode active material slurry on the surface of the conductive substrate, form a film, and dry to obtain a positive electrode sheet; the adhesive is potassium water glass or sodium water glass.
4. The method for preparing the cement-based structural battery with integrated load-bearing and energy storage according to claim 3 is characterized in that: The positive electrode material is one or more of nickel hydroxide, transition metal, transition metal oxide, and transition metal hydroxide; the conductive agent is one or more of graphite and carbon nanotube; The modulus of water glass is 2.0-3.3; the solvent is water; The mass ratio of the positive electrode material, the conductive agent and the binder is (8-9.5): (0.5-1): (3-6).
5. The method for preparing the cement-based structural battery with integrated load-bearing and energy storage according to claim 3, characterized in that: The mass ratio of the positive electrode material to the solvent is (8-9.5): (0.4-0.8); The coating amount of the positive electrode active material slurry is 0.3-0.4 g / cm 2 ; The positive electrode active material slurry is coated on both surfaces of the conductive substrate; The conductive agent is divided into two parts, one part is mixed with the positive electrode material, and the other part is mixed with the binder and the solvent; The conductive substrate is foamed nickel, copper foil or aluminum foil.
6. The method for preparing the cement-based structural battery with integrated load-bearing and energy storage according to claim 1, characterized in that: The negative electrode sheet in step 3) is prepared by the following method: uniformly mixing the negative electrode active material, the conductive agent and the binder to obtain the negative electrode active material slurry; coating the negative electrode active material slurry on the surface of the conductive substrate, forming a film, and drying to obtain the negative electrode sheet; the binder is one or more of potassium water glass and sodium water glass.
7. The method for preparing the cement-based structural battery with integrated load-bearing and energy storage according to claim 6, characterized in that: The negative electrode active material is one or more of iron, iron oxide, ferroferric oxide, carbonyl iron, ferrous sulfide, bismuth sulfide, zinc, zinc oxide, zinc-containing alloy, and iron-containing alloy; The conductive agent is one or more of carbon nanotubes and graphite; The coating amount of the negative electrode active material slurry is 0.35-0.45 g / cm 2 ; The mass ratio of the negative electrode active material, the conductive agent and the binder is (7.5-10): (0-0.5): (3-5.5); The conductive substrate is foamed nickel, copper foil or aluminum foil.
8. The method for preparing the cement-based structural battery with integrated load-bearing and energy storage according to claim 1, characterized in that: The cement slurry containing the liquid-solid mixed phase is prepared under stirring conditions at a stirring speed of 135 to 165 r / min; In step 1), the mixing time at 90-95°C is 1-2 minutes; the cooling to 2-5°C means cooling to 2-5°C within 5-10 minutes; after adding cold water and cooling to 2-5°C, stirring and mixing are performed, and the stirring and mixing time is 15-20 minutes; The step 1) of mixing the solution of the polymer and the strong base, cement and fine sand at 90-95°C means stirring the polymer, the strong base and water at 85-95°C at a speed of 250-260r / min for 1.5-2h to prepare a solution; dry mixing the cement and fine sand at 90-95°C at a speed of 60-70r / min for 5-10min to obtain a cement-fine sand mixture; mixing the above solution and cement-fine sand mixture at 90-95°C; The mass ratio of the cold water to the polymer is (60-80):(8-10).
9. The method for preparing the cement-based structural battery with integrated load-bearing and energy storage according to claim 1, characterized in that: In step 1), the strong base is one or more of KOH and NaOH; the sulfide is one or more of Na2S or K2S; the chemical cross-linking agent is one or more of tetraethylammonium chloride and polyethylene glycol diglycidyl ether; The molecular weight of the polymer PVA is 1000-10000, and the molecular weight of PAA is 10000-500000; The curing in step 4) refers to closed curing at 0°C to 3°C for 6-24 hours; the standing in step 4) refers to room temperature for 12 hours to 24 hours.
10. A cement-based structural battery with integrated load-bearing and energy storage functions prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Cement-based electrochemical energy storage device and preparation method thereof
CN115719681A
Nickel-cobalt sulfide / ferric oxide energy storage device based on in-situ growth and preparation method and application of nickel-cobalt sulfide / ferric oxide energy storage device
CN118116746A
High-ion-conductivity cement-based structured electrolyte and preparation method thereof
CN119638304A
Electrolyte mixture, useful to prepare lithium-ion cells, comprises polypyrrole, conducting salt e.g. lithium hexafluorophosphate, aprotic solvent or mixture of e.g. dimethoxyethane and ethylene carbonate, and mineral additive e.g. cement
DE102008040941A1
Cold-curing type inorganic coating material
JP2000086934A